Suppressing bubble shielding effect in shock wave lithotripsy by low intensity pulsed ultrasound - Wang, Jen-Chieh (2014)
Extracorporeal shock wave lithotripsy (ESWL) has been used as an effective modality to fragment kidney calculi. Because of the bubble shielding effect in the pre-focal region, the acoustic energy delivered to the focus is reduced. Low pulse repetition frequency (PRF) will be applied to dissolve these bubbles for better stone comminution efficiency. In this study, low intensity pulsed ultrasound (LIPUS) beam was aligned perpendicular to the axis of a shock wave (SW) lithotripter at its focus. The light transmission was used to evaluate the compressive wave and cavitation induced by SWs without or with a combination of LIPUS for continuous sonication. It is found that bubble shielding effect becomes dominated with the SW exposure and has a greater significant effect on cavitation than compressive wave. Using the combined wave scheme, the improvement began at the 5th pulse and gradually increased. Suppression effect on bubble shielding is independent on the trigger delay, but increases with the acoustic intensity and pulse duration of LIPUS. The peak negative and integral area of light transmission signal, which present the compressive wave and cavitation respectively, using our strategy at PRF of 1 Hz are comparable to those using SW alone at PRF of 0.1 Hz. In addition, high-speed photography confirmed the bubble activities in both free field and close to a stone surface. Bubble motion in response to the acoustic radiation force by LIPUS was found to be the major mechanism of suppressing bubble shielding effect. There is a 2.6-fold increase in stone fragmentation efficiency after 1,000 SWs at PRF of 1 Hz in combination with LIPUS. In summary, combination of SWs and LIPUS is an effective way of suppressing bubble shielding effect and, subsequently, improving cavitation at the focus for a better outcome.